Migration, Security, and Human Rights: The Struggle for Refugee Protection - Wibisono, Rizky Bangun (The Sunan Ampel Review of Political and Social Sciences, 2024)
This paper aims to examine the complex interplay between migration, human rights, and security, focusing on the recent trends in state responses to refugee protection and the implications for international human rights standards. A qualitative analysis of current literature, policy documents, and case studies was conducted to assess the evolving political dynamics surrounding migration. The study also evaluates the roles of international organizations, such as the United Nations High Commissioner for Refugees (UNHCR), and non-governmental organizations (NGOs) in shaping refugee protection norms. Results: The findings reveal a significant rollback in state commitments to refugee protection, driven by rising nationalism and security concerns. This regression has resulted in the implementation of restrictive migration policies that prioritize national interests over humanitarian obligations, leading to increased vulnerability for displaced populations. The analysis highlights the critical role of NGOs and international bodies in advocating for refugee rights, despite facing challenges from state-centric approaches and power imbalances. Conclusions: The paper concludes that addressing the challenges at the intersection of migration, human rights, and security requires a concerted effort among states, civil society, and international organizations. By fostering collaboration and recognizing the human rights implications of migration, it is possible to develop more inclusive and compassionate policies that uphold the dignity and well-being of refugees and asylum seekers in a rapidly changing global context. give a great title for this article